5-Isopropyl-2-methylphenol enhances penile function in spontaneously hypertensive rats - Tays Amanda Felisberto Gonçalves, Priscilla Maria Pereira Maciel, Larissa Ivone Melo Villanueva, Pablo Ferreira dos Santos, Ismael de Lima Oliveira Júnior, Robson Cavalcante Veras, Islania Giselia Albuquerque Araújo, Isac Almeida de Medeiros (Journal of Applied Pharmaceutical Science, 2024)
5-Isopropyl-2-methylphenol, a monoterpene found in essential oils from various plants, has been shown to have anti-inflammatory, antioxidant, vasorelaxant, and hypotensive effects. The current study looked at the effects of 5-isopropyl-2-methylphenol on male hypertensive rats with erectile dysfunction. During 4 weeks, 12-week-old spontaneously hypertensive rats (SHR) were given intragastrically with saline, 5-Isopropyl-2-methylphenol (50 or 100 mg/kg/day), or sildenafil (1.5 mg/kg/day). Wistar Kyoto rats were utilized as normotensive controls. All the drugs examined throughout the treatment period lowered systolic blood pressure. Treatments with 5-isopropyl- 2-methylphenol and sildenafil enhanced the intracavernosal pressure/mean arterial pressure ratio in hypertensive rats. The acetylcholine sodium nitroprusside-induced relaxation responses in isolated rat corpora cavernosa were considerably improved by sildenafil or 5-isopropyl-2-methylphenol treatments—treatment with 5-isopropyl- 2-methylphenol reduced hypercontractility produced by phenylephrine or electric field stimulation in corpora cavernosa SHR. The contractile response of rats treated with 5-isopropyl-2-methylphenol was not affected in the presence of tempol. The fluorescence intensity emitted by the dihydroethidium probe in rat corpora cavernosa was considerably lower in SHR-treated groups compared to SHR-control. The present study suggests that 5-isopropyl- 2-methylphenol enhances SHR erectile performance while decreasing endothelial dysfunction, smooth muscle cell hypercontractility, and superoxide anion production.
Keywords: Corpus cavernosum, erectile dysfunction, reactive oxygen species, SHR